2018 IEEE International Conference on Systems, Man, and Cybernetics (SMC) 2018
DOI: 10.1109/smc.2018.00106
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Error Detection via Deep Learning

Abstract: Deep learning techniques have revolutionized the field of machine learning and were recently successfully applied to various classification problems in noninvasive electroencephalography (EEG). However, these methods were so far only rarely evaluated for use in intracranial EEG. We employed convolutional neural networks (CNNs) to classify and characterize the error-related brain response as measured in 24 intracranial EEG recordings. Decoding accuracies of CNNs were significantly higher than those of a regular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The IPL might be involved in the information sampling and selection processes (e.g., Baddeley, 2000), and thus the more firstorder memory-related inputs received from the precuneus, the higher and more accurate confidence rating would be. The PrG or a broader presupplmentary motor area (pre-SMA) region, which interconnects with the DLPFC and ACC, might be involved in cognitive control processes (Morales et al, 2018;Völker et al, 2018), and thus when conflicting signals are detected, this region might access more first-order memory-related information from the precuneus to guide a more accurate confidence rating. Therefore, our findings on the relationship of the right IPL -precuneus and right PrG -precuneus rs-FCs with mnemonic metacognitive ability lend support to the hypothesis that mnemonic metacognition relies on the read out of memory trace (Nelson & Narens, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The IPL might be involved in the information sampling and selection processes (e.g., Baddeley, 2000), and thus the more firstorder memory-related inputs received from the precuneus, the higher and more accurate confidence rating would be. The PrG or a broader presupplmentary motor area (pre-SMA) region, which interconnects with the DLPFC and ACC, might be involved in cognitive control processes (Morales et al, 2018;Völker et al, 2018), and thus when conflicting signals are detected, this region might access more first-order memory-related information from the precuneus to guide a more accurate confidence rating. Therefore, our findings on the relationship of the right IPL -precuneus and right PrG -precuneus rs-FCs with mnemonic metacognitive ability lend support to the hypothesis that mnemonic metacognition relies on the read out of memory trace (Nelson & Narens, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that in most cases, shallower fully convolutional models outperformed their deeper counterpart and architectures with residual connections. However, the authors later found the weight initialization to be critical in successfully training deeper architectures such as ResNet on an intracranial task [210], suggesting hyperparameter tuning might be key to using deeper architectures on neurophysiological data (personal communication, April 17, 2019).…”
Section: Deep Learning Methodologymentioning
confidence: 99%
“…They additionally can be applied to the raw EEG data, greatly simplifying the design of BCI pipelines. We further demonstrated the usefulness of CNNs for error decoding from noninvasive (Völker et al, 2018c) and intracranial EEG (Völker et al, 2018b).…”
Section: Introductionmentioning
confidence: 82%